2021
DOI: 10.1111/bjh.17889
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal pathophysiological abnormalities in steady state and after vaso‐occlusive crisis in murine sickle cell disease

Abstract: We showed in the present study that, not unlike in adult patients with sickle cell disease (SCD), Townes mice exhibit increases in serum intestinal fatty acid binding proteins and lipopolysaccharides (LPS), together with a breach in the intestinal barrier. These abnormalities increased rapidly after the induction of vaso-occlusive crisis (VOC). We also confirmed higher intestinal microbial density in SCD. These findings support the concept that SCD and/or its complications, and not hospitalisation or medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…SCD patients exhibit increased abundance of Veillonella that correlated with the frequency of VOC [40], and reduced Alistipes and Pseudobutyrivibrio [41], that are producers of short-chain fatty acids (SCFAs) needed for intestinal health. Intestinal microbial density is also increased in SCD [38,42]. Changes in bacterial composition and density exacerbate the intestinal injury induced by VOC.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…SCD patients exhibit increased abundance of Veillonella that correlated with the frequency of VOC [40], and reduced Alistipes and Pseudobutyrivibrio [41], that are producers of short-chain fatty acids (SCFAs) needed for intestinal health. Intestinal microbial density is also increased in SCD [38,42]. Changes in bacterial composition and density exacerbate the intestinal injury induced by VOC.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…The end-result of the event is the adherence of the sickle erythrocytes to activated leukocytes immobilized on the endothelium, causing microvascular occlusion, vaso-occlusive crisis (VOC), and tissue ischemia. VOC, when involving the splanchnic vasculature, damages the intestinal epithelium [36], as indicated by the elevated serum iFABP levels in SCD [37,38], and increased intestinal permeability. The local hypoxemia may also be responsible for the altered intestinal microbial composition in SCD [39].…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…Recent studies in sickle cell disease (SCD) in mice [76,77] and in humans [78,79] have highlighted the presence and the role of disrupted gut barrier functions in affecting the phenotypes of the disease. This has been associated with intestinal dysbiosis that is characterized by a lower abundance of Alistipes and Pseudobutyrivirio [80].…”
Section: Ongoing Fmt Studies In Patients With Hematologic and Oncolog...mentioning
confidence: 99%
“…This decrease in intestinal barrier integrity can ultimately lead to the translocation of bacterial products into circulation that may exacerbate chronic inflammation in SCD, contributing to worsened disease outcomes. Recent studies in SCD patients and mouse models have demonstrated gut dysbiosis, 7 , 10 elevated markers of intestinal barrier dysfunction 8 , 11 , 12 and protective effects of intestinal microbiome depletion. 9 , 13 , 14 , 15 , 16 In this study, we add to the growing body of evidence for a “leaky gut” phenotype in SCD.…”
Section: Introductionmentioning
confidence: 99%